Application and Demand Model of 5G Communication Technology in Hydrology - LIU Yunshan; LIU Xunhua; GUO Dongrong (Renmin Zhujiang)
In the context of hydrological modernization,the existing communication technology is unable to support the ever-increasing requirements.At present,the application of 5G in many fields has achieved good results.However,there is no in-depth analysis and research on its application situation in the hydrological industry and the demand of the hydrological industry based on 5G.Depending on the analysis of the station network,informatization status and communication technology application regarding hydrology in Ganzhou,the pilot application of 5G in Ganzhou demonstrates that 5G communication technology has obvious advantages over the current communication technology in terms of high-definition video surveillance,hydrological factors monitoring and software system.The analysis of hydrological demand based on 5G yields that demand points for 5G are mainly reflected in hydrological monitoring,equipment technology,video surveillance,software system,hydrological services and Internet of Things related to hydrology,hydrological management and other scalable business.The connection between demand points is also established to build a demand model of 5G-based intelligent hydrology.Noteworthily,the mature application of 5G in the hydrological field to support intelligent hydrology still suffers from some problems,such as low industrialization of support equipment,high cost,small signal coverage and difficult talent training.The next research direction is also proposed in this paper.